Randomized clinical trial comparing the efficacy of vaginal misoprostol and Foley catheter for cervical ripening and induction of labour - Thakur, A; Uprety, D; Yadav, P; Dahal, P; Thaku, D (Health Renaissance, 2011)
Keywords: Prostaglandin; Foley catheter; cervical ripening; induction of labour DOI: http://dx.doi.org/10.3126/hren.v9i2.4980 Health Renaissance 2011: Vol.9 (No.2): 88-90